Relationship between partner’s comparative superiority, relationship behaviors, and relationship satisfaction in couples - Legkauskas, Visvaldas (Psichologija, 2007)
Relationship satisfaction is one of the main determinants of the stability of couple relationships. The past two decades witnessed a growing number of studies of factors affecting relationship satisfaction in couples, including both behavioural aspects and subjective factors. However, the influence of various aspects of the experience of the previous relationship on relationship satisfaction in later relationships has been studied much less extensively. In particular, there have been no studies on how the perceived superiority of the current partner over the previous partner might affect relationship satisfaction in the current relationship. The purpose of the present study was to supplement the body of research with data on the relationship between partner’s comparative superiority, relationship behaviours, and relationship satisfaction in dating couples. Subjects in the present study were 51 heterosexual couple in a dating relationship. Age of the subjects ranged from 19 to 28 years. Couples were selected for this study under the condition that the present relationship was not the first experience of steady dating relationship for either of the partners. Subjects were given a battery of instruments, which included Perceived Relationship Quality Components scale (Fletcher et al., 2000) for measurement of relationship satisfaction, Partner’s Comparative Superiority scale constructed specifically for the present study, and a number of questions on frequency of various relationship behaviours, including sex, signs of attention given to and received from the partner, yelling by the partner or by the subject, not talking by the partner or to the partner and amount of time spent together with the partner. Correlation between relationship satisfaction and partner’s comparative superiority was strong and highly significant (r = 0.656, p < 0.001). There were also significant positive correlations between relationship satisfaction and amount of time spent together with the partner (r = 0.275, p < 0.01), number of signs of attention given to the partner (r = 0.220, p < 0.05) and number of signs of attention received from the partner (r = 0.253, p < 0.05). On the other hand, relationship satisfaction correlated negatively with such behavioural indicators of conflict as the frequency of yelling by the partner (r = –0.341, p < 0.001), not talking by the partner (r = –0.197, p < 0.05) and frequency of the subject yelling at the partner (r = –0.298, p < 0.01). To assess the relative importance of partner’s comparative superiority and behavioural aspects of the relationship to relationship satisfaction, multiple regression analysis was conducted. The final regression equation indicated that only two variables – partner’s comparative superiority and the number of signs of attention given by the subject to the partner – made a significant unique contribution towards explaining the variance of relationship satisfaction. The two variables accounted for 45.6 per cent of the variance of relationship satisfaction, of which 42.5 per cent was accounted for by partner’s comparative superiority.